Tax Morale, Religiusitas, dan Sanksi Pajak Terhadap Tax Compliance Pada WPOP di Organisasi Nahdlatul Wathan - Alvina Windy Pihany; Sri Andriani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The purpose of this study was to determine the effect of Tax Morale, Religiosity, and Tax Sanctions on Tax Compliance of Individual Taxpayers (WPOP). This study uses quantitative methods using primary data sources. The number of samples used in this study was 100 respondents using the multiple regression analysis methods. This research is processed using SPSS software. The results in this study indicate that first (1) tax morality, religiosity, and tax sanctions have a positive and significant effect on taxpayer compliance simultaneously. Second (2) the variables of tax morality, religiosity, and tax sanctions have a positive and significant effect on partial taxpayer compliance. Third (3) the tax morale variable is the most dominant independent variable influencing taxpayer compliance.